Visual Memory in People with Epilepsy- The Neglected Front!! - Ramanujan, Bhargavi; Tripathi, Manjari (Neurology India)
Cognitive impairment is known to occur in persons with epilepsy (PWE); certain aspects of cognition, like executive functions, language and memory may particularly be affected, as has been reported in the literature. The authors of the paper "Prevalence and Factors Influencing Visual Memory Dysfunction among Epilepsy Patients- A Single Center Study" have assessed visual memory among PWE, and have found that over a third of their subjects had "extremely low" visual memory scores. Memory and intelligence outcome following surgery for intractable temporal lobe epilepsy: Relationship to seizure outcome and evaluation using a customized neuropsychological battery.